Three Novel Sequential Reactions for the Facile Synthesis of a Library of Bisheterocycles Possessing the 3-Aminoimidazo[1,2-a]pyridine Core Catalyzed by Bismuth(III) Chloride - Shahrisa, Aziz; Esmati, Somayeh (Synlett, 2013)
Novel, one-pot, two-step, sequential protocols for the synthesis of 1,4-phenylene bisheterocyclic compounds have been developed. Successive sequencing of the Groebke–Blackburn–Bienaymé reaction with Ugi-azide, Hantzsch and Biginelli reactions results in rapid and efficient formation of bisheterocyclic compounds. A simple, fast and high yielding method for the synthesis of 3-aminoimidazo[1,2-a]pyridines catalyzed by bismuth(III) chloride under solvent-free conditions is reported. Bismuth(III) chloride is also an efficient catalyst for the Ugi-azide reaction under solvent free conditions.
Keywords: sequential reactions; Groebke–Blackburn–Bienaymé reaction; 1,4-phenylene bisheterocyclic compounds; Ugi-azide reaction; bismuth(III) chloride; solvent-free reactions